Enhancing the Efficiency of Horizontal Axis Wind Turbines Through Optimization of Blade Parameters - Hossein Seifi Davari; Ruxandra Mihaela Botez; Mohsen Seify Davari; Harun Chowdhury (Journal of Engineering)
In this research, we delve into the promising potential of horizontal axis wind turbines to effectively meet the electricity needs of developing countries. By addressing the challenges posed by low Reynolds number airflow characteristics, we focus on specific airfoils—E471, S2055, and RG15—tailored for horizontal axis wind turbine blade optimization. Utilizing QBLADE software, we evaluate the lift coefficient, stall angle of attack, and lift-to-drag ratio coefficient efficiency of these airfoils across various thickness-to-camber ratios. The aerodynamic efficiency of the altered airfoils is assessed in terms of lift coefficient, drag coefficient, lift-to-drag ratio coefficient, and stall angle of attack at Reynolds number ranging from 50,000 to 500,000. The findings reveal that the optimized thickness-to-camber ratio results in peak lift-to-drag ratio coefficient values surpassing the reference airfoils across the Re range. These lift-to-drag ratio coefficient enhancements vary among airfoils and Re values. Furthermore, modifications to the E471, S2055, and RG15 airfoils increase the peak lift coefficient and stall angle of attack values across all Re ranges examined. The validation of results is achieved through comparison with experimental testing, solidifying the reliability of QBLADE software in predicting aerodynamic performance.